Faculty Contracts in Post-Soviet Countries - Androushchak, Gregory; Yudkevich, Maria (International Higher Education, 2012)
For decades, universities in Soviet countries were governed, evaluated, and financed according to the same principles. The current system is not like this former one. However, faculty contractsa core element in any universitystill participate much in common. While this article is based on detailed data on the academic profession in Armenia, Kazakhstan, Latvia, and Russia, the described trends are, to some extent, common for all post-Soviet countries.